Equal strain on all parts [compact disc] - Buffett, Jimmy (Mailboat/Sun Records, 2023)
Singer/songwriter Jimmy Buffett regaled audiences for over five decades with songs about the faces and places from his lifelong journey along the road less traveled. His upcoming album Equal Strain On All Parts is a new chapter in that story as a playful and heartfelt gift to his dedicated fans. Inspired by his grandfather's description of a good nap, the album features some well-known friends, including Paul McCartney, Emmylou Harris, Angelique Kidjo, and the Preservation Hall Jazz Band.